Adesão terapêutica aos Sistemas de Pressão Positiva em doentes com Síndrome da Apneia Obstrutiva do Sono: uma revisão da literatura portuguesa. - Mara Sofia Freitas Cabilhas (2021)
Introduction: Positive Airway Pressure (PAP) is the gold standard treatment for Obstructive Sleep Apnea (OSA). However, the success of this treatment is limited by nonadherence, which ranges from 30% to 60%. With this review we aimed to summarize and describe all the methods used to evaluate and measure PAP adherence and calculate the adherence in Portuguese population. Materials and Methods: A narrative review was conducted using Repositórios Científicos de Acesso Aberto de Portugal database in order to find studies containing information regarding PAP adherence in OSA patients. The methods of each study were compiled and their main results were organized and displayed in a table and a scatterplot. Additionally, a non-weighted mean was calculated. Results: The methods and terminology used to define, assess and measure adherence were not uniform. Several studies point out that the most used adherence goal is outdated. Therefore, they used higher cut offs or create new clusters based on adherence pattern. Adherence ranged between 54% and 94%. Nonadherence due to discontinuation ranged between 11% and 25%. Discussion: The variability of methods used, as well as the heterogeneity of the studies, have impaired their comparability, which can explain the results' variability. Adherence rate might be overestimated because some studies may reflect an intervention, personalized follow-up protocols or suboptimal cut offs. Conclusion: It seems necessary to do more epidemiological research in this field, as well as to review and update all the process and methods behind PAP adherence.